2021
DOI: 10.1016/j.jbc.2021.100951
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoproteins L1-6 share key cation channel-regulating residues but have different membrane insertion and ion conductance properties

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…APOL6 is a lipid-binding protein with the BH3 domain. It mediates apoptosis through interaction with members of the Bcl-2 family and affects the innate immunity of different microbial pathogens ( Liu et al, 2005 ; Pant et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…APOL6 is a lipid-binding protein with the BH3 domain. It mediates apoptosis through interaction with members of the Bcl-2 family and affects the innate immunity of different microbial pathogens ( Liu et al, 2005 ; Pant et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…APOL4 is a member of the lipoprotein L family, which encodes a protein that may play a role in the reverse transport of cholesterol from peripheral cells to the liver and in the transport and exchange of lipids throughout the body. The APOL gene family is thought to be innate immune genes that evolved rapidly in the primate lineage, and their expression is upregulated by proinflammatory signals [ 5 , 6 ]. It has been reported that APOL4 may be a prognostic marker for breast cancer [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apolipoprotein L4 (APOL4), a member of the lipoprotein L family, encodes a protein that may exert an action in reverse cholesterol transport from peripheral cells to the liver, as well as in lipid transport and exchange throughout the body ( ) (accessed on 11 January 2022). The APOL gene family is thought to be innate immune genes that have evolved rapidly in the primate lineage, and their expression is upregulated by pro-inflammatory signals such as interferon, tumor necrosis factor alpha and viral mimics [ 5 , 6 ]. Previous study has illustrated that lipid metabolism is largely reprogrammed in cancer and that most types of cancer use lipids and cholesterol to meet their unlimited energy needs and the demands of increased membrane biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…ApoL-I is 43 kDa in molecular weight. The apolipoprotein L gene family includes ApoL1–6 [ 187 ]. APOL-I and APOL-II co-localize with ApoA-I in HDL particles and play important roles in lipid exchange, transport and movement in the kidneys [ 188 , 189 ].…”
Section: Roles and Biological And Pathological Functions Of Apolipopr...mentioning
confidence: 99%